COMMUNITY AND NUTRITIONAL DISORDERS IN CHILDREN BETWEEN 6 AND 12 YEARS OF AGE IN SANTA CLARA, VILLA CLARA, CUBA - Borroto-Mederos, Yumenet (2022)
The present research work was carried out in the health area 19-6 of the Camacho Libertad Popular Council, in the city of Santa Clara, province Villa Clara, Cuba, between November 12, 2018 and February 24, 2019. The research took into account children between the ages of 6 and 12 years old, as well as their parents, because they were considered to be largely responsible for the food consumed at home. In this sense, they were intentionally involved in the workshops designed in the company of their children. For the realization of the research, different theoretical and empirical methods were put into practice in their dialectical interrelation, which allow to verify the most frequent nutritional disorders detected in the health area and the social need to prevent them, through the implementation of the system of workshops designed to solve the problem under study. The proposal was evaluated as pertinent by the external evaluators consulted and was implemented with excellent results in the study area selected for this purpose. Through these activities, spaces for exchange and reflection on the importance of knowing aspects related to children's nutritional nutrition were created. This linkage of cooperation and sensitization, allows a rapprochement of the inhabitants of the Camacho Libertad popular council with the researchers. Keywords: food – Popular Council – nutrition – workshops – nutritional disorders